The detection efficiency study of NaI(Tl) scintillation detector with the different numbers of SiPMs - Bao Wang; Xiongjie Zhang; Qingshan Wang; Dongyang Wang; Dong Li; Mingdong Xiahou; Pengfei Zhou; Hao Ye; Bin Hu; Lijiao Zhang (Nuclear Engineering and Technology, 2022)
SiPMs are generally coupled into whole columns in gamma energy spectrum measurement, but the relationship between the distribution of whole SiPM columns and the energy resolution of the measured energy spectra is rarely reported. In this work, ∅ 3 × 3 inch NaI scintillator is placed on an 8 × 8 SiPM array, and the energy resolution of the 137Cs peak at 662 keV corresponding to the γ-ray is selected as a reference. Each SiPM is switched to explore the influence of the number of SiPM arrays, distribution position, and reflective layer on the energy resolution of SiPMs. Results show that without coupling, the energy resolution is greatly improved when the number of SiPMs ranges from 4 to 32. However, after 32 slices (the area covered by SiPMs relative to the scintillator reaches 25.9%), the improvement in energy resolution and total pulse count is not obvious. In addition, the position of SiPMs relative to the scintillator does not exert much impact on the energy resolution. Results also indicate that by adding a reflective film (ESR), the energy resolution of the tested group increases by 10.38% on average. This work can provide a reference for the design and application of miniaturized SiPM gamma spectrometers.